2008
DOI: 10.1097/01.ncc.0000305766.42475.33
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Hope Among Early Female Survivors of Childhood Cancer via the Internet

Abstract: The purpose of this research was to establish the feasibility of delivering the Hope Intervention Program (HIP) using a Web-based design among 6 female survivors of childhood cancer. The HIP is an 8-week program to foster and promote hope. Each session of the HIP has specific focus, goals, and activities that offer opportunities for participants to share and discuss issues of importance to them. The HIP was delivered online with the use of educational software that included Web cameras and voice and text chat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 26 publications
0
55
0
2
Order By: Relevance
“…Logsdon and Gohmann (2008) suggested that pilot studies can be invaluable in testing recruitment procedures, establishing costs of recruitment, and obtaining baseline data on study measures and demographic data. Evaluation data generated from the pilot study suggested that using a Web-based approach was effective in the delivery of the intervention as evidenced by participants’ evaluation of the program (Cantrell & Conte, 2008). Study participants’ comments suggested that the online sessions promoted intimate, meaningful, human-to-human interactions to foster hope and build a trusting relationship among group members (Cantrell & Conte, 2008).…”
Section: Study Protocolmentioning
confidence: 99%
“…Logsdon and Gohmann (2008) suggested that pilot studies can be invaluable in testing recruitment procedures, establishing costs of recruitment, and obtaining baseline data on study measures and demographic data. Evaluation data generated from the pilot study suggested that using a Web-based approach was effective in the delivery of the intervention as evidenced by participants’ evaluation of the program (Cantrell & Conte, 2008). Study participants’ comments suggested that the online sessions promoted intimate, meaningful, human-to-human interactions to foster hope and build a trusting relationship among group members (Cantrell & Conte, 2008).…”
Section: Study Protocolmentioning
confidence: 99%
“…Several interventions incorporated asynchronous communication, such as use of e-mail or bulletin boards that enabled text-based communication outside of real time, whereas only a few used some form of synchronous conferencing that allowed realtime interaction. One example is the web-based Hope Intervention Program (HIP), which used a voice over Internet protocol to conduct a multimedia session with small groups that included audio and video through use of web cameras (22). Less commonly used forms of new media included blogs or video sharing and only one intervention for adolescent survivors of childhood cancer incorporated electronic or video games (40).…”
Section: New Media Elements Of Interventionsmentioning
confidence: 99%
“…1,2 Moreover, with a recent high funding priority on innovation of research, an increasing number of researchers began to develop and test various types of Web-based interventions in diverse areas including self-management education for older adults with type 2 diabetes, 1 smoking cessation program for adolescents, 2 and physical activity promotion of adults with metabolic syndrome. 3 Web-based interventions in health-related areas could be categorized into education programs, 1,4 decision support systems, 5,6 support groups, 7,8 and games. [9][10][11] Education programs are targeted to provide a Web version of traditional education programs and access to the educational materials through the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Support groups provide a medium for users to share their experiences and opinions through the Internet and obtain peer support (eg, chat rooms, bulletin boards, e-mail, online discussion forums, and/or text messages). 7,8 Games may provide educational aids to enhance skills and knowledge for users and to assist users' decision making. [9][10][11] These different types of Web-based interventions are not mutually exclusive; rather, they are combined in many cases.…”
Section: Introductionmentioning
confidence: 99%